Pengaruh Motivasi Kerja, Keterikatan Kerja Dan Budaya Organisasi Terhadap Kesiapan Berubah Karyawan BPJS Kesehatan Magelang - Mochamad Syarifudin; Nur Wening (Lembaga Pengembangan Kinerja Dosen, 2024)
The objectives of this study include: (1) Analyzing the effect of work motivation on employee readiness to change at BPJS Kesehatan Magelang; (2) Analyzing the effect of work attachment on employee readiness to change at BPJS Kesehatan Magelang; and (3) Analyzing the effect of organizational culture on employee readiness to change at BPJS Kesehatan Magelang. This research uses quantitative descriptive method. Data were collected using a questionnaire given to all permanent employees at BPJS Kesehatan Magelang as many as 48 people. Based on the results of the study, the following conclusions were obtained: (1) There is an influence of work motivation on employee readiness to change; (2) There is an influence of work attachment on employee readiness to change; and (3) There is an influence of organizational culture on employee readiness to change. As an improvement effort, it is recommended to BPJS health to maintain the work motivation of its employees and maintain the organizational culture that has been implemented at this time.